Art and Disability - Wexler, A. author. aut Link
XVII, 248 p.
Keywords: Wexler argues that the arts are most effective when they are in service of social growth, critical to identity formation. This book balances theory with practical knowledge and offers critical research that challenges the biases regarding the nature of art and education.